Unilateral Calcification of the Caudate and Putamen: Association with Underlying Developmental Venous Anomaly - Dehkharghani, S.; Dillon, W.P.; Bryant, S.O.; Fischbein, N.J. (American Journal of Neuroradiology, 2010)
SUMMARY: Stenosis of a DVA may result in chronic venous ischemia. We present 6 patients (3 men, 3 women; age range, 30–79 years; mean age, 53 years) with unilateral calcification of the caudate and putamen on noncontrast CT. This calcification typically spared the anterior limb of the internal capsule. No patient presented with symptoms referable to the basal ganglia or had an underlying metabolic disorder or other process associated with calcium deposition. All patients subsequently underwent gadolinium-enhanced MR imaging and/or CTA or conventional angiography demonstrating the presence of an adjacent DVA. We hypothesize that chronic venous ischemia in the drainage territory of the DVA causes the abnormal mineralization. Greater recognition of this entity will prevent misinterpretation of this finding as acute hemorrhage and will prevent unnecessary and sometimes invasive evaluation in such patients. Furthermore, this entity should be considered in the differential diagnosis of unilateral basal ganglia hyperattenuation. AVMarteriovenous malformationCcaudateCa2+calcificationCTACT angiographyDVAdevelopmental venous anomalyHAheadacheICHintracerebral hemorrhageLleftNAnot applicablePputamenRrightSZseizure